The Relation Between Social Support and Adherence to the Treatment of Hypertension - Mohammad Taher; Hamid Abredari*; Mahmood Karimy; Ahmadreza Abedi; Morteza Shamsizadeh (Hamadan University of Medical Sciences, 2014)
Background and Objectives: Although social support seems to be effective in adherence to the treatment of hypertension, its effects in hypertensive patients have not been well documented. The current study tried to clarify the relationship between social support and adherence to the treatment in patients with hypertension. Materials and Methods: This cross-sectional study applied census sampling to recruit all eligible patients with hypertension (130 patients). A demographic questionnaire, the Hill-Bone Compliance to High Blood Pressure Therapy Scale, and the Social Support Behaviors Scale were used to collect data. Spearman's correlation coefficient, t-test, and analysis of variance were conducted to analyze the data. All analyses were performed in SPSS-16. Results: Poor, moderate, and acceptable adherence to the treatment was detected in 9.2%, 85.4%, and 5.4% of the patients, respectively. There was a significant relationship between social support and level of compliance with the treatment regimen, i.e. patients with moderate-high levels of social support had higher adherence to the treatment. Moreover, subjects with poor compliance were found to have poorer social support. Social support was also found to be significantly related with level of education and marital status. Conclusion: This study highlighted the role of social support as a determinant of adherence to the treatment in patients with hypertension. Therefore, attention to social support can increase hypertensive patients' adherence to treatment regimens and improve their health status.